Idea "dwóch prędkości" w UE25, ..., 27, ..., 28, ..., n to tylko teoria czy konieczność? Wybrane aspekty w kontekście odnowionego w 2005 r. Lizbońskiego Programu Wspólnoty "Wspólne przedsięwzięcia dla wzrostu i zatrudnienia" - Pluciński, Eugeniusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The main focus of this paper is interdependence between policy and economics of the EU with a view to The Common Market and Lisbon Strategy. The analysis is performed in the context of idea for dual-speed economic integration. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 241-254